Bronchial Asthma and Allergic Rhinitis (Eurasian Medical Research Periodical, 2022)
138 patients aged 18 to 70 years were included in the study to study the course and level of control over the disease, indicators of quality of life (QOL) and cytokine profile in patients with bronchial asthma (BA) in combination with allergic rhinitis (AR). In the observed patients, drug (34.3% vs 12.1%) and food (34.3% vs 15.2%) allergies were significantly more common than in patients with isolated BA. The majority of patients (65.7%) had an uncontrolled course of BA. The negative effect of BA in combination with AR on the QoL of patients was shown. Thus, the revealed relationship between QOL parameters and the result of the AST test, as well as the level of cytokines in the blood serum (IFN-γ, IL-8) in the observed patients, allows us to consider these parameters as criteria for controlling the course of asthma